FORMULASI DISPERSAN MINYAK BUMI DARI SURFAKTAN DIETANOLAMIDA (DEA) DAN METIL ESTER SULFONAT (MES) - Wica Elvina, Erliza Hambali, dan Mohamad Yani (Department of Agroindustrial Technology, Bogor Agricultural University, 2016)
Utilisations of surfactant from palm oil, such as diethanolamide (DEA) and methyl ester sulfonate (MES) develope for variety products. One of the potential utilisations from both surfactants is a product of petroleum dispersant (oil spill dispersant/OSD). This research conducted to find a formulation for produce the OSD product. OSD formulation of this research had been found. Nonionic surfactant was DEA solution, and anionic surfactant was MES solution, both of surfactant mixed on various concentrations and certain ratio, with heated at 50°C for 60 minutes. The OSD product was analysedfor emulsion stability, density, surface tension, pH, and viscosity. The best product was applied to simulation testing on oil pollution of seawater. The best result of OSD formulation was at ratio 1 : 3 and the formulated of DEA 3% and MES 5%. The OSD productwas indicated good stability (>80%) with physical and chemical properties of density of 0.90 g/cm3, surface tension of 25.59 mN/m, pH of 9.1, and the viscosity of 131 cP. The testing result of applied OSD simulation for oil pollutin handling in seawater (10 mL/L) showed the dispersed ability for oil spill was good (>80%). The mixture of oil spill and OSD soluble on seawater showed significant increase of COD and BOD value. Keywords: diethanolamide (DEA), methyl ester sulfonate (MES), Oil Spill Dispersant (OSD), surfactant